Governance and Audit Quality: Can Improve Earnings Quality? - Erwin Saraswati; Ariestya Alfianti Puteri (Universitas Muhammadiyah Malang, 2023)
Purpose: This study aims to examine the effect of governance structure and audit quality on earnings quality. Methodology/Approach: 74 manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2011 to 2019 was selected using purposive sampling and used to test the hypotheses. The data was analyzed using OLS within multiple linear regression approach. Findings: Regression results showed independent commissioners and numbers of audit committee meetings improved earnings quality in large-sized manufacturing companies. This study also found that institutional ownership has no effect on earnings quality. Likewise, audit quality, as reflected by size of the public accounting firm, has no effects on earnings quality. Practical Implications: The results provide information about the importance of independent commissioners in keeping good earnings quality. These findings can be used either by the government or investors to strengthen the role of independent commissioners. Also, the government can regulate the minimum number of audit committee meetings to overcome low-income quality problems. Originality/value: This study proved that internal independence mechanism is the crucial one to attain a high level of earnings quality. Also, this study differentiates the effect of predictors by company’s size.